Fluorescence diagnosis of pre-tumor and tumor pathology of endometrium - E. V. Filonenko; O. V. Chulkova; E. G. Novikova; L. G. Serova (Biomedical Photonics)
The technique of fluorescence hysteroscopy with Alasens includes visual assessment of fluorescence of Alasens-induced protoporphyrin IX and local fluorescence spectroscopy. The technique allows to improve the efficacy of early diagnosis for endometrial pathology including early endometrial cancer, to assess definitely an extent of pre-tumor and tumor process. The sensitivity of fluorescence hysteroscopy accounts for 100%, the specificity – 98%.